Integration of Local Wisdom Values in Early Childhood Collaborative Learning Strategies: A Study on Culture-Based Early Childhood Education - Mutiara, Yolanda; Juliana, Anisa; Wulandari, Rahma; Ambarwati, Flora; Rahmawati, Suciyana (BUHUTS AL ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This study aims to explore the integration of local wisdom values in collaborative learning strategies for early childhood education in culture-based institutions. Local wisdom values, such as cooperation, tolerance, and respect for parents, are an important part of cultural identity that can be instilled early on through a contextual and meaningful learning approach. This study uses a qualitative approach with a case study method in several early childhood education institutions that carry the concept of local culture-based education. Data were collected through observation, in-depth interviews, and documentation. The study's results indicate that integrating local wisdom into collaborative learning strategies can strengthen children's social character, increase their involvement in group activities, and foster cultural awareness from an early age. The learning strategies implemented involve traditional games, folklore, and community-based activities that support cooperation and noble values. These findings recommend the importance of teacher training to understand and apply local wisdom-based learning approaches as an effort to enrich the educational process that is relevant to the child's social and cultural context